2016
DOI: 10.14814/phy2.12835
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the short-term substrate utilization response to high-carbohydrate and high-fat meals in the whole-body indirect calorimeter

Abstract: The paper demonstrates that minute‐to‐minute metabolic response to meals with different macronutrient content can be measured and discerned in the whole‐body indirect calorimeter. The ability to discriminate between high‐carbohydrate and high‐fat meals is achieved by applying a modified regularization technique with additional constraints imposed on oxygen consumption rate. These additional constraints reduce the differences in accuracy between the oxygen and carbon dioxide analyzers. The modified technique wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Studies to determine the blood active GIP and GIP(3-42) levels are required to clarify the precise effects on GIP/GIPR signaling activity after ingestion of steamed WB and arabinoxylan. Increased blood glucose and insulin levels also reduce fat oxidation [4648]. While the postprandial blood insulin response was similar, the blood glucose response tended to be lower after WB feeding in the present study.…”
Section: Discussionsupporting
confidence: 48%
“…Studies to determine the blood active GIP and GIP(3-42) levels are required to clarify the precise effects on GIP/GIPR signaling activity after ingestion of steamed WB and arabinoxylan. Increased blood glucose and insulin levels also reduce fat oxidation [4648]. While the postprandial blood insulin response was similar, the blood glucose response tended to be lower after WB feeding in the present study.…”
Section: Discussionsupporting
confidence: 48%
“…Due to lack of data on the effect of polyphenols on fat oxidation, this study was conducted as a pilot study. The target enrollment was n = 16 based on previous calorimetry studies at the Beltsville Human Nutrition Research Center [ 22 ]. Additional subjects were enrolled due to weather related electrical disruptions in data collection.…”
Section: Methodsmentioning
confidence: 99%
“…It has previously been shown that RER could be a prognostic marker of weight loss and a predictor of weight gain [15,16]. Moreover, minute-to-minute RER measured in a respiratory chamber calorimeter showed that the slopes of RER were different in response to different dietary interventions [17]. However, although RER is currently the preferred method for determining metabolic fuel, it is a time-consuming, uncomfortable, and costly and impractical tool for real-time day-to-day assessments of metabolic activity.…”
Section: Principal Findingsmentioning
confidence: 96%